(untitled) (Pedagogy of Higher and Secondary Education, 2021)
The article determines the essence of competence approach during foreign languages’ study at the institute of higher education, exposes a foreign language teacher’s key competences, considers the aims of foreign languages’ study at the aspect of the mentioned approach.